(untitled) (American Journal of Pedagogical and Educational Research, 2023)
In the article, if we consider the social imagination, mood, behavioral norms, experiences, knowledge, needs, values and ideals of the Uzbek people under the influence of the unity of nationality and universality in the Uzbek national mentality, be scientifically analyzed that they all contain elements of nationality and universality.